Providing the Resources by using scheduling algorithm in Cloud Computing - Lavanya, B. Muni (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is an environment for providing different services on the premise of demand and the need. It can able to build the virtualization, distributed computing to assist the cost-efficient usage method to adequate the resources with the usage of resource scalability, computing resources and on-demand resources. It can manage the user requests and also make available the resources by implementing the new virtual machines. The virtual machine can qualify for assigning the resources premises on the availability of resources. Cloud computing assists to load balancing and avoid the delay in running of the job. Based on the characteristics of the job new virtual machines are implemented. This paper can deal with the assigning of resources to the job based on its requirement and also consider the priorities of the job. Here we distinguish the various types of leases with their corresponding priorities. According to that priority, the execution can be processed. The main aim of this work is to delay the low priority job (consists high deadline of the job) and schedule the high priority job (having a low deadline of the job) and dynamically allocates VM resources to the user job within the deadline